Analisis Timbulan dan Karakteristik Sampah Mudah Terbakar di TPA Banjarsari Kabupaten Bojonegoro sebagai Bahan Baku Refuse Derived Fuel - pramudia, Fiqo; Afrianisa, Rodu Dhuha (Institut Teknologi Adhi Tama Surabaya, 2024)
The amount of waste entering the Banjarsari Bojonegoro landfill reaches 65 tons per day. Bojonegoro people have a waste generation coefficient of 0.4 kg/person/day. When multiplied by the entire population of Bojonegoro Regency, which is 1.3 million, the waste becomes 520 tons per day. This study aims to utilize the waste pile at TPA Banjarsari as RDF fuel. According to the research findings, the total waste generation taken into TPA Banjarsari was 53,420 kg/day, with plastics (22.09%), fabrics (4.16%), wood (5.07%), paper (5.15%), rubber/leather (1.15%), organics (56.21%), glass (0.74%), metal (1.18%), and others (4.24%). Combustible waste generation at TPA Banjarsari was 20,299.6 kg/day, or 37.6%. Based on an analysis of the waste characteristics, the types of wood that met the RDF standards of the Ministry of Industry in 2017 had a moisture content value of 18.06%, an ash content of 1.29%, a volatile matter content of 66.99%, and a calorific value of 3,788.51%. The waste reduction in scenario 1 (scavengers) yielded 400.07 kg/day, or 0.74%, and residue of 53,019.96 kg/day, or 99.26%. Meanwhile, the waste reduction in scenario 2 (RDF) gained 4,300.31 kg/day, or 8.05%, and residue of 49,199.69 kg/day, or 91.94%. Last, the optimal waste reduction obtained 4,813.19 kg/day, or 9.02%, and residue of 48,606.81 kg/day, or 90.98%.